The impact of implementing electronically integrated risk-based business licensing services on service quality - Hapsari, Fitri Yunianto; Riau, Dwi Putranto; Aripin, Sofjan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The provisions of Law No.11 of 2020 concerning Job Creation stipulate the use of the Risk-Based Business Licensing Service System (OSS RBA), which regulates licensing based on the level of business risk. However, its implementation in the Investment Management Unit and One-Stop Integrated Services of the South Jakarta Administrative City is still experiencing obstacles so that the goal of improving service quality has not been achieved. The purpose of this study was to analyze the influence of electronic-based licensing service implementation factors on the quality of public services at UP PMPTSP South Jakarta Administrative City. This study uses an explanatory method with a quantitative approach to analyze the relationship between the implementation of risk-based electronic licensing services (RBA OSS) and public service quality at UP PMPTSP South Jakarta Administrative City. Using purposive sampling, 100 respondents who utilized the RBA OSS system in 2023 were selected. Data collection involved a 5-point Likert scale-based questionnaire, observations, and interviews, with validity and reliability confirmed through factor loading, AVE, Cronbach's Alpha, and Composite Reliability. SEM-PLS analysis revealed that communication, resources, disposition, and bureaucratic structure significantly enhance service quality, while the community role, though positive, was not significant. The study concludes that communication, resources, disposition, and bureaucratic structure significantly improve the quality of licensing services at UP PMPTSP South Jakarta Administrative City, with a collective influence of 91.3%. However, the public's role, while positive, does not significantly affect service quality. Future research should explore ways to increase community engagement and examine the long-term effects of these reforms on public satisfaction and business growth.